Quantification of tissue shrinkage and dehydration caused by microwave ablation: experimental study in kidneys for the estimation of effective coagulation volume - Sommer, Christof-Matthias; Sommer, Steffen A.; Mokry, Theresa; Gockner, Theresa; Gnutzmann, Daniel; Bellemann, Nadine; Schmitz, Anne; Radeleff, Boris; Kauczor, Hans-Ulrich; Stampfl, Ulrike; Pereira, Philippe L. (Journal of vascular and interventional radiology, 2013)
Purpose - To quantify the extent of tissue shrinkage and dehydration caused by microwave (MW) ablation in kidneys for estimation of effective coagulation volume. - Materials and Methods - MW ablations were carried out in ex vivo porcine kidneys. Six study groups were defined: groups 1A, 2A, and 3A for MW ablation (90 W for 5 min, 7.5 min, or 10 min), and groups 1B, 2B, and 3B for control (without MW ablation). Pre- and postinterventional volume analyses were performed. Effective coagulation volumes (original tissue included in coagulation) were determined. Postinterventional dehydration analyses were performed with calculation of mean mass fractions of water. - Results - Mean deployed energies were 21.6 kJ ± 1.1 for group 1A, 29.9 kJ ± 1.0 for group 2A, and 42.1 kJ ± 0.5 kJ for group 3A, and were significantly different (P < .0001). Differences between pre- and postinterventional volumes were −3.8% ± 0.6 for group 1A, −5.6% ± 0.9 for group 2A, and −7.2% ± 0.4 for group 3A, and −1.1% ± 0.3 for group 1B, −1.8% ± 0.4 for group 2B, and −1.1% ± 0.4 for group 3B. Postinterventional volumes were significantly smaller than preinterventional volumes for all groups (P < .01). Underestimations of effective coagulation volume from visualized coagulation volume were 26.1% ± 3.5 for group 1A, 35.2% ± 11.2 for group 2A, and 42.1% ± 4.9 for group 3A, which were significantly different (P < .01). Mean mass fractions of water were 64.2% ± 1.4 for group 1A, 63.2% ± 1.7 for group 2A, and 62.6% ± 1.8% for group 3A, with significant differences versus corresponding control groups (P < .01). - Conclusions - For MW ablation in kidneys, underestimation of effective coagulation volume based on visualized coagulation volume is significantly greater with greater deployed energy. Therefore, local dehydration with tissue shrinkage is a potential contributor.